Simulation of Nanoindentation of Single and Multiple Coating Layers for Automotive Bearings - W.Zamri, Wan Fathul Hakim; Mohamed, Intan Fadhlina; Bakri, Khairunas; Md Din, Muhamad Faiz (International Journal of Engineering and Technology, 2018)
A coating is capable of changing the resistance to wear. This study focused on the simulation of the nanoindentation of AISI440C steel coated with single and multiple layers of TiN and TiSiN. TiN and TiSiN coatings are often used for tools and equipment, especially for the automotive bearing. The main objective of this study was to identify the mechanical properties for single coating layers of TiN and TiSiN by means of a nanoindentation simulation using ANSYS Mechanical APDL software. Most mechanical failures are due to stress factors, as defined by the mechanical properties of the material concerned. Nevertheless, information on the mechanical properties of coating materials is still limited, especially for TiN and TiSiN. Therefore, this study analysed the response of the materials under pressure from an indenter tip to obtain their mechanical properties. The lack of information about researches into the mechanical properties and response of coating materials, when subjected to a load, makes it necessary to conduct a study of the techniques of the layered coating. Among the mechanical properties that were considered were the elastic modulus, Poisson’s ratio, yield strength, and hardness of the material.